2005
DOI: 10.1111/j.1440-1827.2005.01827.x
|View full text |Cite
|
Sign up to set email alerts
|

Berry splenic artery aneurysm rupture in association with segmental arterial mediolysis and portal hypertension

Abstract: A rare case of berry splenic artery aneurysm (SAA) rupture associated with segmental arterial mediolysis (SAM) and portal hypertension is reported. A 66-year-old woman, diagnosed as having liver cirrhosis and portal hypertension 6 years earlier, suddenly developed a lancinating pain in the upper abdomen and lost consciousness. She recovered consciousness while being transferred to hospital by ambulance. During the investigations, her level of consciousness suddenly deteriorated. Ultrasonography showed a massiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Other causes of ruptured splenic artery aneurysms include congenital causes such as anomalous origin [8], Berry aneurysm [9] and arteriovenous malformation [10] and acquired conditions such as pancreatitis [11] and possible toxic causes resulting in vessel wall damage [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Other causes of ruptured splenic artery aneurysms include congenital causes such as anomalous origin [8], Berry aneurysm [9] and arteriovenous malformation [10] and acquired conditions such as pancreatitis [11] and possible toxic causes resulting in vessel wall damage [12]. …”
Section: Discussionmentioning
confidence: 99%
“…The disease most commonly involves visceral arteries such as the superior or inferior mesenteric, splenic, hepatic and renal arteries in the elderly 3,9 . The patients usually complain of sudden abdominal pain, abdominal distention, vital abnormalities and unconsciousness 9–11 . It has also been reported that several intracranial aneurysms were due to SAM 12–14 .…”
mentioning
confidence: 99%
“…It has also been reported that several intracranial aneurysms were due to SAM 12–14 . The etiology of SAM is poorly understood, but it is thought that vasospasm is relevant 1,3,4,7,10 . Complication with autoimmune diseases such as microscopic polyangiitis (MPA) has also been reported 15,16 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the aneurysms are caused by degenerative atherosclerosis, portal hypertension secondary to liver cirrhosis, pancreatitis, pregnancy, congenital causes such as anomalous origin, Berry aneurysm, arteriovenous malformation [2,9,7,11,5,10].…”
mentioning
confidence: 99%